Selection of Non-vitamin K Antagonist Oral Anticoagulant for Stroke Prevention in Atrial Fibrillation Based on Patient Profile: Perspectives from Vietnamese Experts. Part 1 - Tri Huynh Quang Ho; Minh That Ton; Viet Lan Nguyen; Hung Manh Pham; Sy Van Hoang; Nhan Thanh Vo; Thai Quoc Nguyen; Linh Tran Pham; Ton Duy Mai; Thang Huy Nguyen (European Cardiology Review)
In Asia, especially Vietnam, AF is a common arrhythmia and is linked to a higher risk of stroke and systemic embolism. Anticoagulation therapy for stroke prevention in AF patients can result in bleeding complications. To effectively manage AF, adopting appropriate anticoagulation and addressing modifiable risk factors are crucial. Vietnamese clinicians are particularly interested in non-vitamin K antagonist oral anticoagulants (NOACs), a recent development in AF treatment. However, the lack of head-to-head trials comparing NOACs makes selecting a specific NOAC challenging. This review aims to provide a comprehensive overview of the available clinical evidence on NOACs for stroke prevention in AF to assist clinicians in making informed decisions and improving treatment outcomes in patients with AF. The first part of this review will present the current landscape of AF in Vietnam, focusing on AF prevalence and highlighting gaps in clinical practice. Furthermore, this part extensively discusses the anticoagulation strategy for both primary and secondary stroke prevention in AF.